2016
DOI: 10.13080/z-a.2016.103.042
|View full text |Cite
|
Sign up to set email alerts
|

Measurements and modelling of wind erosion rate in different tillage practices using a portable wind erosion tunnel

Abstract: Artificial intelligence systems are widely accepted as a technology providing an alternative method to solve complex and ill-defined problems. Artificial neural network (ANN) is a technique with a flexible mathematical structure, which is capable of identifying a complex nonlinear relationship between the input and output data. The objective of this study was to investigate the relationship between dust concentration and wind erosion rate, and to illustrate how ANN might play an important role in the predictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In the same way, Labiadh et al [27] showed that the difference in the sediment flux was about a factor 4 between agricultural surfaces tilled with a disc plough and a tiller plough and was of an order of magnitude between surfaces tilled with a disc plough and a moldboard plough. More recently, the impact of tillage practices on dust emission was also evidenced by Çarman et al [28] using a portable wind erosion tunnel in an experimental field in Turkey. Eight different tillage applications were tested: conventional tillage, six different reduced tillages, and direct seeding.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the same way, Labiadh et al [27] showed that the difference in the sediment flux was about a factor 4 between agricultural surfaces tilled with a disc plough and a tiller plough and was of an order of magnitude between surfaces tilled with a disc plough and a moldboard plough. More recently, the impact of tillage practices on dust emission was also evidenced by Çarman et al [28] using a portable wind erosion tunnel in an experimental field in Turkey. Eight different tillage applications were tested: conventional tillage, six different reduced tillages, and direct seeding.…”
Section: Introductionmentioning
confidence: 64%
“…Indeed, tilled surfaces present ridges that allow the trapping of a part of the saltating particles into the furrow of the ridges, which reduces the saltation of soil grains and consequently decreases the sediment flux blowing over tilled surfaces. Thus, this decrease of the wind erosion efficiency over different tilled surfaces is dependent on the geometric characteristics of the tillage ridges, i.e., ridge height (RH) and ridge spacing (RS), e.g., [24][25][26][27][28]. As an example, Armbrust et al [25] showed that any size ridge up to 20.3 cm height on a cultivated soil is more effective in controlling wind erosion than is a smooth surface.…”
Section: Introductionmentioning
confidence: 99%
“…The results were of approximately 2.5 mg•m −3 and 4.5 mg•m −3 for PM 10 and PM 5 , respectively, at the monitoring station found at 10 m altitude [2]. Carman et al (2016) [17] concluded that PM 10 concentration for seven different tillage applications in clay-loam soil conditions generally increased with the intensity of tillage operations. They examined the relationship between the wind erosion rate and dust concentration using artificial neural networks (ANNs) and discovered that the ANNs model consistently provided better predictions.…”
Section: Introductionmentioning
confidence: 89%
“…To evaluate the performance of the results obtained with both ANNs and polynomial models, root mean square error (RMSE), coefficient of determination (R 2 ), and relative error (ε) were utilized and calculated using the following equations [17,37]:…”
Section: Evaluation Of Model Performancementioning
confidence: 99%
“…After each run, the sediment was collected; oven dried at 105°C, and weighed on a balance. To obtain the wind erosion rate (g m-2 h-1), the mass of the sediment (g) was divided by the test area (m2) and event duration (h) (Zamani and Mahmoodabadi, 2013;Çarman et al 2016). Measurements were made once after one day from tillage in both years.…”
Section: Methodsmentioning
confidence: 99%